PENGARUH KUALITAS PRODUK, NILAI PELANGGAN, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE IPHONE - admin, DEA DARA PIRANTI B11111131 (Jurnal Manajemen Update, 2016)
This study aimed to analyze the effect of product quality, consumer value, and brand image to the iPhone purchasing decision. Respondents in this study were students in the Tanjungpura University, Pontianak who using iPhone. Type of this research is using survey method and the nature of causality. The technique of data collected is using questionnaires with nonprobability Sampling technique by means of purposive sampling. The population in this study is the students ofÂ  Tanjungpura University, Pontianak force in 2014 that uses the iPhone, and samples were taken for study as many as 100 people. Data analysis technique used is the homepage regression analysis using SPSS version 16.0 for Windows. The findings of this study indicate that the variable quality of the product, consumer value, and brand image have significant and positive impact on the purchase decision. 33.7% variable purchase decision can be explained by the NII in the independent variables, while the variables remaining 66.3% is explained by other variables outside of this research. Keywords: product quality consumer value, brand image, purchasing decision. Â